2021
DOI: 10.1039/d0py01128b
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive rose bengal-based latex via RAFT emulsion polymerization-induced self-assembly

Abstract: Copolymerization of acrylic acid (AA) with a photosensitizer-based comonomer by reversible addition fragmentation transfer (RAFT) polymerization produces reactive stabilizer for emulsion polymerization induced self-assembly (PISA). This polymerization in aqueous dispersed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Boussiron et al further investigated the inclusion of rose bengal into self-assembled nanoparticles to determine the optimum position of the photocatalytic material within the self-assembled nanoparticle. 56 Boussiron et al demonstrated the easy incorporation of the photoactive material into both environments, combining multiple different monomers. 56 Independent on the location of the photoactive monomer sub 100 nm particles were again formed.…”
Section: Self-assembled Polymer Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boussiron et al further investigated the inclusion of rose bengal into self-assembled nanoparticles to determine the optimum position of the photocatalytic material within the self-assembled nanoparticle. 56 Boussiron et al demonstrated the easy incorporation of the photoactive material into both environments, combining multiple different monomers. 56 Independent on the location of the photoactive monomer sub 100 nm particles were again formed.…”
Section: Self-assembled Polymer Photocatalystsmentioning
confidence: 99%
“…56 Boussiron et al demonstrated the easy incorporation of the photoactive material into both environments, combining multiple different monomers. 56 Independent on the location of the photoactive monomer sub 100 nm particles were again formed. No particular difference in the photooxidation reaction of furfuryl alcohol was observed when RB was found in the core, corona or as a free molecule.…”
Section: Self-assembled Polymer Photocatalystsmentioning
confidence: 99%
“…Save and co-workers reported the synthesis of photosensitizing nanoparticles via PISA using thermally mediated reversible addition−fragmentation chaintransfer (RAFT) polymerization. 43,44 The RB photosensitizer was functionalized with a polymerizable handle to covalently anchor it to the nanoparticles during PISA. Boyer and coworkers demonstrated the capability of applying a porphyrinbased photosensitizer as both a photoinduced electron-transfer (PET) catalyst for PISA by RAFT and as an 1 O 2 generator.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several reports have demonstrated the feasibility of synthesizing photoactive nanoparticles by PISA. Save and co-workers reported the synthesis of photosensitizing nanoparticles via PISA using thermally mediated reversible addition–fragmentation chain-transfer (RAFT) polymerization. , The RB photosensitizer was functionalized with a polymerizable handle to covalently anchor it to the nanoparticles during PISA. Boyer and co-workers demonstrated the capability of applying a porphyrin-based photosensitizer as both a photoinduced electron-transfer (PET) catalyst for PISA by RAFT and as an 1 O 2 generator. , Building upon these methods, our strategy is to employ Rose Bengal methacrylate (RBMA), which contains the RB photosensitizer simultaneously as a monomer and as a photocatalyst in PET-RAFT polymerization to achieve self-catalyzed PISA.…”
Section: Introductionmentioning
confidence: 99%
“…Reversible addition–fragmentation chain transfer (RAFT)-mediated polymerization-induced self-assembly (PISA) has recently emerged as an efficient in situ growth strategy for the preparation of block copolymer nanoparticles with various morphologies such as spheres, worms, vesicles, ordered inverse morphologies, and so on. RAFT-mediated PISA can be performed at room temperature via either photoinitiation or redox initiation for the preparation of temperature-sensitive block copolymer nanoparticles. Moreover, the reaction media of RAFT-mediated PISA can be water, alcohols, or nonpolar solvents, allowing the preparation of block copolymer nanoparticles with diverse surface properties. However, further surface modification of block copolymer nanoparticles is still challenging since there are no reactive groups on the surface.…”
mentioning
confidence: 99%